Design, Synthesis, and Bioactivity Study of Novel Tryptophan Derivatives Containing Azepine and Acylhydrazone Moieties - Jingjing Zhang; Rongxin Yang; Lili Li; Jianhua Liu; Yuxiu Liu; Hongjian Song; Qingmin Wang (Molecules, 2022)
Based on the scaffolds widely used in drug design, a series of novel tryptophan derivatives containing azepine and acylhydrazone moieties have been designed, synthesized, characterized, and evaluated for their biological activities. The bioassay results showed that the target compounds possessed moderate to good antiviral activities against the tobacco mosaic virus (TMV), among which compounds 5c, 6a, 6h, 6t, 6v, and 6y exhibited higher inactivation, curative, and protection activities in vivo than that of ribavirin (40 ± 1, 37 ± 1, 39 ± 2% at 500 mg/L). Especially, 6y showed comparable activities to that of ningnanmycin (57 ± 2, 55 ± 3, 58 ± 1% at 500 mg/L). Meanwhile, we were pleased to find that almost all these derivatives showed good larvicidal activities against Plutella xylostella. Meanwhile, these derivatives also showed a broad spectrum of fungicidal activities.